PENGARUH PEMAHAMAN PAJAK, TARIF PAJAK, LINGKUNGAN, DAN KESADARAN SUBJEK PAJAK TERHADAP KEPATUHAN SUBJEK PAJAK UMKM DI KECAMATAN PONDOK AREN - Galih Chandra Kirana; Azys Prasstia; Heriston Sianturi; Meifida Ilyas (Jurnal Liabilitas, 2024)
The purpose of this study is to determine the impact of tax understanding, tax rates, environment and taxpayer awareness on MSME taxpayer compliance. in a quantitative way. The data used are primary data obtained from a questionnaire and distribution of respondents to her MSME taxpayers in Pondok Allen District, and the sample is her 99 respondents. Based on the results obtained in analytical testing, it is concluded that taxpayer awareness and taxpayer awareness of taxes, tax rates and the environment simultaneously influence tax compliance. And each independent variable has a partial influence on the dependent variable.